Effects of individual and combined dietary weight loss and exercise interventions in postmenopausal women on adiponectin and leptin levels. (29th March 2013) - Abbenhardt, C.; McTiernan, A.; Alfano, C. M.; Wener, M. H.; Campbell, K. L.; Duggan, C.; Foster‐Schubert, K. E.; Kong, A.; Toriola, A. T.; Potter, J. D.; Mason, C.; Xiao, L.; et al.
Abstract Background Excess body weight and a sedentary lifestyle are associated with the development of several diseases, including cardiovascular disease, diabetes and cancer in women. One proposed mechanism linking obesity to chronic diseases is an alteration in adipose‐derived adiponectin and leptin levels. We investigated the effects of 12‐month reduced calorie, weight loss and exercise interventions on adiponectin and leptin concentrations. Methods Overweight/obese postmenopausal women (n = 439) were randomized as follows: (i) a reduced calorie, weight‐loss diet (diet; N = 118), (ii) moderate‐to‐vigorous intensity aerobic exercise (exercise; N = 117), (iii) a combination of a reduced calorie, weight‐loss diet and moderate‐to‐vigorous intensity aerobic exercise (diet + exercise; N = 117), and (iv) control (N = 87). The reduced calorie diet had a 10% weight‐loss goal. The exercise intervention consisted of 45 min of moderate‐to‐vigorous aerobic activity 5 days per week. Adiponectin and leptin levels were measured at baseline and after 12 months of intervention using a radioimmunoassay. Results Adiponectin increased by 9.5% in the diet group and 6.6% in the diet + exercise group (both P ≤ 0.0001 vs. control). Compared with controls, leptin decreased with all interventions (diet + exercise, −40.1%, P < 0.0001; diet, −27.1%, P < 0.0001; exercise, −12.7%, P = 0.005). The results were not influenced by the baseline body mass index (BMI). The degree of weight loss was inversely associated with concentrations of adiponectin (diet, P‐trend = 0.0002; diet + exercise, P‐trend = 0.0005) and directly associated with leptin (diet, P‐trend < 0.0001; diet + exercise, P‐trend < 0.0001). Conclusion Weight loss through diet or diet + exercise increased adiponectin concentrations. Leptin concentrations decreased in all of the intervention groups, but the greatest reduction occurred with diet + exercise. Weight loss and exercise exerted some beneficial effects on chronic diseases via effects on adiponectin and leptin.